Perancangan APAR dan Hidran Halaman pada Gedung Laboratorium - Djafar, Alfian; Kholiq Deliasgarin Radhyantho; Gad Gunawan; Ridhwan Haliq; Fajar Habib Syarifudin; Ersamada Sinaga (Journal Serambi Engineering, 2024)
Fire protection can increase work safety and security factors from fire hazards. Therefore, this research aims to design a fire protection system in an integrated laboratory building. The fire protection design is active fire protection, namely yard hydrants and fire extinguishers. This research uses technical research methods. The standards used refer to NFPA 14, NFPA 24, Regulation of PER.04/MEN/1980, and SNI 03-1375-2000. The Fire extinguisher design is carried out by determining the minimum required number of fire extinguishers and the type content used. The design of yard hydrants is carried out by determining the minimum number of yard hydrants needed. Based on the research results, the fire extinguishers planned on the 1st floor require 22 pieces, while the 2nd and 3rd floors each require 12 fire extinguishers. Based on the fire class, the recommended APAR is the dry chemical powder and CO2. The number of yard hydrants required is 9, the groundwater tank volume is 130 m3, and the discharge obtained is 0.04 m3/s with a total head of 54,342 m. So, the appropriate pump specification is the Ebara brand centrifugal pump Type 150x125 FS4LA with a power of 54,342 kW.